Cultural Intermediaries - Hutchinson, Jonathon. author. aut Link
XIX, 236 p. 16 illus., 15 illus. in color.
Keywords: This book interrogates the existing theories of convergence culture and audience engagement within the media and communication disciplines by providing grounded examples of social media use as a social mobilization tool within the media industries. As digital influencers garner large audiences across platforms such as YouTube and Instagram, they sway opinions and tastes towards often-commercial interests. However, this everyday social media practice also presents an opportunity for socially and morally motivated intermediaries to impact on public issues. Cultural Intermediaries: Audience Participation in Media Organisations is intended to provide an explicit overview of how one notable media organization, the Australian Broadcasting Corporation (ABC), incorporates participation into its production methodology, while maintaining its role as a public service media organisation. The book provides several cases studies of successful audience participation across socially motivated projects. Finally, the book provides an updated framework to understand how cultural intermediation can facilitate authentic audience participation in media organisations.